Câncer de boca e orofaringe em Belo Horizonte: estudo de base hospitalar no período de 2005 a 2015 - Andrea Maria Lopez Soto (2017)
The aim of this study was to identify the profiles of patients with oral and oropharyngeal cancer referred to the Department of Head and Neck Surgery in a public hospital in Belo Horizonte, from 2005 to 2015. Medical records from the hospital were reviewed and the variables studied were age, gender, skin color, years of education, marital status, selfreportedhome address, smoking status, alcohol consumption, histopathologic diagnostic, the primary tumor location, the type of treatment, tumor staging, and dates of first, last consult, and surgery. Descriptive data analyses of all variables were performed, the sociodemographic and clinical variables were compared by type of cancer and type of treatment with a chi-square test, in addition to spatial analysis and geo-visualization of the Belo Horizontes resident cases. In total 289 medical records were evaluated, most of the patients were males (227), white (117) and married (125), the average age was 58.6 years old. A low educational level was frequent among the subjects and the place ofresidency of 72.7% of subjects was Belo Horizontes metropolitan area. Tobacco smoking and alcohol consumption were identified in 85.1% and 82.0% of the patients, respectively. The base of the tongue, the soft palate, the floor of the mouth, the palatoglossal arch, and the lateral border of the tongue were the most frequent localization sites. Squamous cell carcinoma was reported in 89.6% patients and 67.8% were diagnosed with stage III or IV (advanced). The mean time elapsed from biopsy result to first appointment at HC/UFMG was 1.5 months (1.7 DS) and the mean time elapsed from first appointment to surgery was 2.9 months (4.4 DS). Oral cancer accounted for 50.5% of the cases, and the remaining 49.5% were oropharyngeal. Analysis of sociodemographic and clinical features in relation to type of cancer revealed that oropharyngeal patients were preferentially smokers, diagnosed at an advanced stage of the disease, with 3 or more sites affected, received non-surgical treatment and were residents more than 50 km away from the hospital. Regarding the type of treatment performed 32.9% were only diagnosed and did not continue with the proposed treatment. When comparing the treatment decision (refuse or receive), the variables associated with the adhesion to treatment were the initial clinical stage (I / II) and married status. The spatial distribution of Belo Horizonte resident patients revealed a higher density of subjects in the Venda Nova, Northeast and Northwest regions although a homogeneous distribution of the basic health units of primary attention in all regions with cancer patients. Lastly, considering the socioeconomic variables (low income and household in semi-adequate conditions), it was observed that the majority of the cases occur in neighborhoods with poor conditions. In conclusion, the sociodemographic profile of patients with oral cancer is not different from those with oropharyngeal cancer treated at a public hospital in Belo Horizonte.